Fitossociologia e interferência da comunidade espontânea sobre a produtividade da cultura do quiabo em sistema orgânico - Santos, Raimundo Nonato Viana (2015)
The work was carried out to study the floristic composition of spontaneous community and periods of interference of these on okra cv culture Valencia in organic system in Sao Luis - MA. The design was a randomized block with the treatments consisted of increasing periods of cohabitation or control of volunteers, from seven days after emergence (DAE) to harvest (74DAE), totaling twenty treatments with four replicates each. Spontaneous community was assessed by the number of individuals and accumulated dry mass of each population in treatments. These data were used to determine the Relative Frequency (Freq. R), Relative Density (De.R) Relative Dominance (Do.R) and the Importance Value Index (IVI). In spontaneous community, dominated the botanical group of eudicotyledonous and families with highest species richness were Poaceae, Cyperaceae and Amaranthaceae most notably during periods of coexistence. The weeds of greater importance value index were Colla, Commelinabenghalensis L., Cynodondactylon (L.) Pers., Eleusineindica L. and Phyllanthusniruri L. Spontaneous community caused yield losses around 51% and assuming 5% tolerance in reducing okra productivity, the period before interference (PAI) was 12 DAE, the total period of interference prevention (PTPI) was 36 DAE and the critical period of interference prevention (PCPI) was 12-36 DAE. Spontaneous community interferes with the productivity of the okra with greater intensity between 12 and 36 DAE